To survive sensibly or to court heroic death : management of Guyana's political economy 1965-85 - Ferguson, Tyrone (Public Affairs Consulting Enterprise GeorgetownGY, 1999)
Presents an account of the stewardship of Forbes Burnham as Premier, Prime Minister and ultimately Executive President of the Co-operative Republic of Guyana. Recounts the performances and failures of the authoritarian government he led, and highlights the conflicts between Burnham's People's National Congress Party (P.N.C.) and Cheddi Jagan's People's Progressive Party (P.P.P.). Looks at the effort to chart a sovereign non-aligned course for the emergent nation. Records Guyana's decolonization and development up to 1985.